An Eco-critical Reading of William Wordsworth's Poetry and Pantheistic Strains in his Poetry (Khairulummah, 2021)
The relation between people and environment has long been documented through literary works. Edward white gives the example of Adam and Eve journey through the Garden of Eden in the Bible and Odyssey dangerous trek across the Mediterranean Sea in Homer’s Odyssey as early literary examples in which human path cross the nature and interact with the beauty of nature.
Keywords: relation, environment, Adam, Garden, Odyssey